Efektivitas Handout Kingdom Protista Berbasis Siklus Belajar 5E pada Kemampuan Berpikir Kritis Siswa - Yossie Ulfa Nuzalifa; Suci Aulia Putri (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: This study aims to analyze and describe the effectiveness of the kingdom Protista handout based on the 5E learning cycle on students' critical thinking skills. This research is a quasi-experimental study with a posttest-only control group design. The population in this study were all students of class X SMA Harapan 3 Medan, while the sample in this study were students of class X MIA A as the experimental class and X MIA B as the control class selected by non-probability sampling using a purposive sampling technique. The data were collected by giving a posttest after the learning process was completed, the instrument used was a critical thinking ability test. The data obtained were analyzed using the independent sample t-test using SPSS software. Based on the research results, the Sig. Levene's Test for Equality of Variances is 0.763, where this value is> 0.05. This means that the variance of the data between the experimental group and the control group is homogeneous or the same. So that the interpretation of the independent sample t-test results table above is guided by the values contained in the